2019
DOI: 10.1016/j.marpetgeo.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the petroleum generation characteristics of Palaeogene source rocks in the Austrian Molasse Basin as revealed by principal component analysis biplots

Abstract: After Rock-Eval & TOC screening and heterogeneity evaluation on 91 Palaeogene source rock samples from a well drilled in the Austrian Molasse Basin, ten shale samples were selected for detailed investigations by means of pyrolysis-gas chromatography, bulk kinetics and biomarker identification and quantification. Afterwards, 2-D biplots based on principal component analysis were applied to unravel the palaeo-environmental control on the development of petroleum source rocks. All samples are immature source rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…However, even in some of the sandy limestones, terrestrial organic particles could be identified, leading to elevated concentrations of TOC in these intervals. Generally, productivity (Totman Parrish and Curtis 1982;Pedersen andCalvert 1990), preservation (Demaison andMoore 1980;Demaison 1991;Vasiliev et al 2019), sedimentation rate (Ibach 1982;Creaney and Passey 1993), and salinity influence (Horsfield et al 1994;Yang and Schulz 2019) are typically considered as the most important factors controlling the organic matter and TOC enrichment in petroleum source rocks (Littke et al 1997). In Plouti section, organic matter is more abundant in the more siliciclastic parts of the section and less common in the more calcareous intervals.…”
Section: Sedimentary Basin Dynamics: Implications For the Onshore Depmentioning
confidence: 99%
“…However, even in some of the sandy limestones, terrestrial organic particles could be identified, leading to elevated concentrations of TOC in these intervals. Generally, productivity (Totman Parrish and Curtis 1982;Pedersen andCalvert 1990), preservation (Demaison andMoore 1980;Demaison 1991;Vasiliev et al 2019), sedimentation rate (Ibach 1982;Creaney and Passey 1993), and salinity influence (Horsfield et al 1994;Yang and Schulz 2019) are typically considered as the most important factors controlling the organic matter and TOC enrichment in petroleum source rocks (Littke et al 1997). In Plouti section, organic matter is more abundant in the more siliciclastic parts of the section and less common in the more calcareous intervals.…”
Section: Sedimentary Basin Dynamics: Implications For the Onshore Depmentioning
confidence: 99%
“…TOC is widely used to analyse the organic matter richness in source rocks (Dang et al, 2016; Hou & Feng, 2011; Nie et al, 2019; Peters & Cassa, 1994; Yang & Schulz, 2019). Table 1 shows TOC values for the 20 target samples from Dalong Formation exhibiting variable richnesses that ranged from 1.18% to 4.35% with an average of 2.53%.…”
Section: Resultsmentioning
confidence: 99%
“…With TOC values ranging from 0.96% to 9.54% for the ten target samples (Table 1), most of the samples can be classified as "Very Good Source Rock (2.0% < TOC < 4.0%)" to "Excellent Source Rock (TOC > 4.0%)" based on their organic matter richness. 32,33 Notably, TOC contents vary among different sedimentary systems. Specifically, the target samples collected from the Daoshanchong section, which were deposited in a tidal flat-lagoon system, exhibited high TOC contents ranging from 7.32% to 9.54% (average 8.42%; Table 1).…”
Section: Bulk Geochemical Characteristicsmentioning
confidence: 99%